In-situ trash management and irrigation methods for enhancing soil fertility of sugarcane (Saccharum officinarum L.) in semi-arid region of India - Basavaraj Biradar; U. S. Surve; A. V. Solanke; S. D. Gorantiwar; V. S. Patil; M. R. Patil; Manajanagouda S. Sannagoudar; Gaurendra Gupta (Annals of Agricultural Research, 2023)
The depleting soil health and crop productivity in the sugarcane cultivating area is a major concern because of reduced yields as result of burning trash after harvest of sugarcane and faulty irrigation management. This necessitates retention of trash and appropriate method of irrigation to effective utilisation of soil and water resources, while concurrently conserving the soil fertility. The field experiment was conducted at Mahatma Phule Krishi Vidyapeeth (MPKV), Rahuri during 2020-21 and 2021-22 on medium black soil with moderately alkaline in soil reaction (8.22), low organic carbon (0.39 %), low available nitrogen (245.64 kg/ ha), medium in phosphorus (22.25 kg/ha) and high in potassium (454.40 kg/ha). The experiment comprising of three levels of trash management practices and four levels of irrigation was laid out in strip-plot design with three replications. The results revealed that nitrogen, phosphorus and potassium uptake by sugarcane was significantly higher in trash management with shredder machine (TMSM) (246.69, 88.81 and 310.83 kg ha-1 in ratoon as compared to farmer’s practice. Among different irrigation method, surface drip irrigation+inverted sprinkler irrigation recorded the significantly higher uptake of NPK (282.4, 107.31 and 361.47 kg ha-1 in plant crop and 265.9, 101.52 and 335.05 kg ha-1 in ratoon crop. Trash management with shredder machine (TMSM) has recorded the highest available NPK (183.20, 24.73 and 461.95 kg ha-1, respectively) at harvest over other trash management practices. Surface drip irrigation+inverted sprinkler irrigation recorded significantly higher availability of NPK (190, 25.65 and 476.92 kg ha-1, respectively) than other irrigation methods. The interaction effect between trash management and irrigation methods were found to be significant. Theses resource management technologies were found very effective for improving the soil fertility and enhancing the yield besides saving of nutrient applied in sugarcane.